PHOSPHORUS AND POTASSIUM DOSES AND ROW SPACINGS ON CRUDE PROTEIN CONTENTS IN PIGEONPEA GRAINS - BERTOLIN, Danila Comelis; SÁ, Marco Eustáquio de; BUZETTI, Salatiér; OLIVEIRA, Letícia Lisboa; LOPES, Elielda Mariane (Scientia Agraria, 2007)
The present work had for objective to evaluate the effects of five phosphorus doses and four potassium doses in two plant spacings inter row in protein contents grains of short-duration pigeonpea, in Selvíria, State of Mato Grosso do Sul, with sowing in januare of 2005. For the treatments effect determination, in a 2 x 5 x 4 factorial was used a completely randomized block design, with four replications, being treatments 30 and 50 cm plant spacings inter row, 0, 40, 80, 120 and 160 kg ha-1 of P2O5 and 0, 30, 60 and 90 kg ha-1 of K2O. The treatments influence in crude protein. The space of 50 cm and 40 kg ha-1 of P2O5 improve the crude protein. The space of 30 cm, 120 kg ha-1 P2O5 dose and 60 kg ha-1 K2O dose increase the yield protein.